O território quilombola é dela. Sobre Nossa Senhora, santos e quilombolas na Vila – Bairro do Carmo São Roque -SP - Abreu, Ana Luísa Nardin Rezende de (Universidade Federal de São Carlos, 2019)
This dissertation deals with the relations between the residents of Carmo neighborhood with Nossa Senhora do Carmo and other saints. The field research was carried out in the city of São Roque in a territory that is in the process of being officially recognized by INCRA as a quilombola area, more precisely, the village of Carmo. Thus, I seek to investigate what Nossa Senhora do Carmo can as protagonist in the life of the blacks, their history, their kinship and their daily lives.I do this by seeking to highlight the female role in the care of the lives of the residents of Carmo, both on the part of women and the Santa itself. The Santa was stolen in March 2012, the robbery and all it involves is an event that strengthens the hypothesis that something is beyond her own image, as mere artifact or object. Nossa Senhora do Carmo is pointed out by the residents as the one that owns and integrates the quilombola territory, which gives it, as it were, unity and meaning. The idea that leads this research is that the saints, and especially Nossa Senhora do Carmo, are with the blacks of Carmo village, as companions in a relationship described as affection and respect. Therefore, I will highlight contexts in which saints and blacks are friends who share anguish, requests, joys, sadness, parties, work, among many other events.
Quilombola territory is her's. About Nossa Senhora, saints and quilombolas in Vila - Bairro do Carmo São Roque -SP
Keywords: Quilombolas; Nossa Senhora do Carmo; Território; Santos; Mulheres; Territory; Saints; Women; CIENCIAS HUMANAS::ANTROPOLOGIA::ANTROPOLOGIA DAS POPULACOES AFRO-BRASILEIRAS